2007
DOI: 10.1097/qad.0b013e3282f08b4d
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of acute HIV-1 infection in sub-Saharan Africa: development of a risk score algorithm

Abstract: Using this algorithm, we could identify 95% of AHI cases by performing nucleic acid or protein tests in only 40% of patients. Risk score algorithms could enable rapid, reliable AHI detection in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
102
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 24 publications
10
102
1
Order By: Relevance
“…32,42,66 A proportion (47%) experienced pain in the 7 days prior to the survey. This period of prevalence of pain, while not as high as other reports for people living with HIV in Southern Africa 27, [43][44][45] (possibly due to prior use of untested tools, measurement among advanced populations, and use of long periods of time), is still higher than the 17% found in a sample of 839 HIV-negative adults attending an urban clinic for sexually transmitted diseases in Malawi, 48 the 33% reported in a community sample in a resource-poor area of Cape Town, South Africa, whose HIV status was unknown, 29 and the 24% reported in a Norwegian general population. 51 This sample frequently experienced pain in the head, chest and abdomen, sites which have been consistently documented in HIV-infected patients.…”
Section: Discussioncontrasting
confidence: 56%
“…32,42,66 A proportion (47%) experienced pain in the 7 days prior to the survey. This period of prevalence of pain, while not as high as other reports for people living with HIV in Southern Africa 27, [43][44][45] (possibly due to prior use of untested tools, measurement among advanced populations, and use of long periods of time), is still higher than the 17% found in a sample of 839 HIV-negative adults attending an urban clinic for sexually transmitted diseases in Malawi, 48 the 33% reported in a community sample in a resource-poor area of Cape Town, South Africa, whose HIV status was unknown, 29 and the 24% reported in a Norwegian general population. 51 This sample frequently experienced pain in the head, chest and abdomen, sites which have been consistently documented in HIV-infected patients.…”
Section: Discussioncontrasting
confidence: 56%
“…Data from Malawi also show that patients with genital ulcerations have almost 6 times the odds of having acute HIV infection compared with other nonulcerative STI patients [7,10]. Our study showed that acute HIV infections were associated with unknown ulcer etiology, genital lymphadenopathy, and absence of a stable partner.…”
supporting
confidence: 54%
“…In very low-risk settings, the yield of primary HIV-1 infections would be expected to be low. Accordingly, investigators have begun attempting to define criteria for targeting NAAT screening to public testing program clients with appreciable risk of having primary HIV-1 infection [38]. Such criteria could make screening for primary HIV-1 infection more attractive, even as public health programs consider expanding 'routine' HIV-1 testing in low-risk healthcare settings.…”
Section: Strategies To Broaden Screeningmentioning
confidence: 99%